(untitled) (Altre Modernità, 2022)
Similar to many other countries, journalistic production in China during the first half of 2020 was dominated on a thematic level by the COVID-19 pandemic. The trend included the mouthpiece of the Central Committee of the Chinese Communist Party (CCP), Renmin Ribao. Its news and commentary articles, which are widely republished by other media, influence the country’s political life, and contribute to the process of meaning generation in the news discourse and to the CCP’s effort to align Chinese citizens to official narratives. Renmin Ribao can therefore provide a relevant source to investigate the relationship between political power and the COVID-19 pandemic, starting from the hypothesis that the paper’s narrative would aim at discursively turning the international health crisis into a piece of positive propaganda. This study aims to verify whether and how the paper did so, and to question the assumption that the outlet’s media discourse can be equated to the CCP official discourse. The research is developed as a case study and blends quantitative and qualitative tools grounded on Applied Linguistics, Discourse-Historical Approach, and Frame Analysis, in order to analyse a corpus of commentaries that have appeared in the outlet’s online edition in 2020. By applying a Genre Analysis approach, the study also offers insights into the possibility to identify distinguishing characteristics and communicative goals in the different sub-genres of Renmin Ribao commentaries.